Short-term effectiveness of auricular vagus nerve stimulation in patients with myofascial pain syndrome - Ünal, Simay; Karagözoğlu Coşkunsu, Dilber; Hatık, Sefa Haktan; Özden, Ali Veysel (The European Research Journal, 2022)
Objectives: To evaluate the effect of auricular vagus nerve stimulation (VNS) applied in addition to ischemic compression and stretching exercises on pain, trigger point (TP) sensitivity, grip strength, quality of life and autonomic functions in patients with myofascial pain syndrome (MPS). Methods: Sixty patients, who had neck pain, met the diagnostic MPS criteria of Travell and Simons were included in the study. The subjects were randomly divided into VNS group (n = 30) or control group (n = 30). Each group performed 10 sessions of TP ischemic compression and stretching exercises (5 days/week). Ten sessions of 30-minute long auricular VNS were added to the treatment in VNS group. Pain severity [Visual Analogue Scale (VAS)], TP sensitivity (algometer), grip strength (Jamar dynamometer), quality of life [Short Form-36 (SF-36)] and autonomic function [Composite Autonomic Symptom Scale-31 (Compass-31)] were evaluated before and after 10 sessions of treatment. Results: The VAS, algometer and Jamar measurements showed significant improvement in both groups. A statistically significant improvement was found in orthostatic intolerance, secretomotor and pupillomotor subscales of Compass-31 scale in the VNS group following the treatment (p < 0.05) while no significant difference was observed in the control group (p > 0.05). The control group showed significant improvement in all parameters of SF-36 scale, while the VNS group showed significant improvement in physical function, social functionality and pain parameters (p < 0.05). The changes in the VAS, algometer, Jamar scores and secretomotor subscale of the Compass-31 scale were statistically higher in the VNS group than in the control group (p < 0.001, p < 0.001, p = 0.001 and p = 0.011, respectively). Conclusions: It can be argued that auricular VNS increases the effectiveness of ischemic compression and stretching exercises in patients with MPS. Further and detailed studies are needed in which the effect of VNS alone or in combination with other treatments in patients with MPS is examined and the physiological mechanisms are investigated.